(untitled) (Al-Aasar, 2025)
This research captures a detailed analysis of the conventional cryptographic techniques and the relatively recent artificial intelligence encryption techniques. Exploring the historical development of encryption and the supplementation of artificial intelligence (AI) applied to cryptography, this paper discusses how AI enriches flexibility, sophistication, and predictive functionalities. Further, the research assesses different encryption methods to identify their security effects, the current development in key management, and the computational complexity. A comparative evaluation of the effectiveness, safety, and susceptibility of using conventional and artificial intelligence-based methods to quantum computing and crypt-analysis breakthroughs is conducted. Therefore, this study seeks to fill the existing research gap of the application of AI and its impact on next-generation cryptography for cyber security.